ANALISA KUALITAS PELAYANAN SISTEM INFORMASI AKADEMIK TERHADAP KEPUASAN PENGGUNA SISTEM DI STMIK PUTERA BATAM - Nur Elfi Husda (Universitas Putera Batam, 2013)
STMIK Putera Batam is an University in Batam who always need to improve the quality of service for both students and faculty as users of the system. In the world of education, especially higher education, information technology into an organization's critical success factors in its development now requires serious treatment in terms of service to the users of educational services. Sistem Informasi Akademik (SIA) is a resource for all things in the form of information that are related to academic issues on campus. SIA than an information resource on campus, can also be used as a means of communication media between lecturer and students, students and students, lecturer with campus officials and anyone who is in the college environment. Problem formulation in this research is the extent of user satisfaction of SIA in STMIK Putera Batam, and what services the factors that most affect the satisfaction system in STMIK Putera Batam. The results showed that the quality of service that consists of 5 variables (Tangibles, Reliability, Responsiveness, Assurance and Empathy) influence on satisfaction of users of system in STMIK Putera Batam and partially there are two variables that significantly influence the system user satisfaction Responsiveness and Empathy. While the most dominant variable affecting the system of user satisfaction in STMIK Putera Batam system is variable Empathy. The relationship between the 5 variables of service quality (Tangibles, Reliability, Responsiveness, Assurance and Empathy) with the satisfaction of users of the system are included in the category of very strong correlation coefficient was found to be 73.4%, so there is a strong positive relationship between the variables of service quality and satisfaction of users of the system